Influencia de la fertilizacion NPK en la produccion de cafe. Resultado prliminar - Gonzalez, C.=700 1 Chala, S.; Almaguer, J.; Diaz, A.
(Es, En)
Ilus., 9 ref.
(Numero Especial)
Keywords: COFFEA ARABICA; ABONOS NPK; PRODUCCION; CUBA; CULTIVOS TROPICALES